2005
DOI: 10.2174/1568016054368205
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venom Metalloproteinase Containing a Disintegrin-like Domain, its Structure-activity Relationships at Interacting with Integrins

Abstract: Snake venom disintegrins represent a family of RGD (Arg-Gly-Asp) or KGD (Lys-Gly-Asp)-containing proteins which have been reported to be unique and potentially useful tools not only for investigating integrin-ligand interactions, but also for the development of anti-thrombotic agents in terms of their anti-platelet activities. Snake venom proteins containing a disintegrin-like domain represent another super-family of proteins in which many of them have been demonstrated to have similar ability to inhibit plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 128 publications
(211 reference statements)
2
22
0
Order By: Relevance
“…This indicated that the peak doubling did not affect the C-terminal region of the sequence. Similar observations were made from the natural abundance 13 C-HSQC spectrum (Fig. 2), which was particularly visible in the methyl group region, presenting many (but not all) replicated cross-peaks.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…This indicated that the peak doubling did not affect the C-terminal region of the sequence. Similar observations were made from the natural abundance 13 C-HSQC spectrum (Fig. 2), which was particularly visible in the methyl group region, presenting many (but not all) replicated cross-peaks.…”
Section: Introductionsupporting
confidence: 82%
“…The full assignment of the backbone nitrogen atoms was possible for species B (= major species in 15 N-rbitistatin sample), whereas 86% of the nitrogen atoms were assigned for bitistatin A using natural abundance 15 N-spectra. Eighty-eight percent and 82% assignment was achieved for the Ca carbons of bitistatins A and B, respectively, via 13 C-HSQC spectra recorded with the natural abundance samples. Only a partial assignment (< 60% of the protons) was possible for minor bitistatin C. The NMR data confirmed that bitistatins A and B have identical primary structure, as well as the regions of bitistatin C that we were able to assign (residues 4-14 and 30-83).…”
Section: Nmr Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metalloproteases in snake venom can cause proteolysis of the extracellular matrix and disrupt cell-matrix and cell-cell adhesion. 42 Integrins, which are critical for cellular adhesion, redistribute away from the basal surface of 16 Venom from snakes of the same genus as the Brazilian lancehead decreased neutral red uptake by Vero cells, another kidney epithelial cell line, indicating impairment of transmembrane transport. 44 In an experimental study, Russell's viper venom caused lysis of vascular smooth muscle cells, mesangiolysis and tubular degeneration with cellular detachment from the basement membrane.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Therefore, it can be hypothesized that silencing of the reprolysin and astacin metalloproteases (within the salivary glands and the midgut) could have indirectly impaired oogenesis by its effect on blood feeding and digestion (Lu et al, 2005;Jia et al, 1996;Sterchi et al, 2008). Since the astacin transcripts are also present in the ovaries and are known to be involved in vital functions such as growth factor activation (Stöcker et al, 1993) and embryo development (dorso-ventral patterning) (Shimell et al, 1991), thus a direct effect on oogenesis cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%